A CASE OF TAKOTSUBO SYNDROME PRECIPITATED BY DIABETIC KETOACIDOSIS - T. Kitpowsong, Anawin; Muhammad, Haris; Ahmad, Sarah Aftab; Chhabra, Lovely; Khalid, Nauman (Journal of Ayub Medical College Abbottabad, 2023)
Takotsubo syndrome (TTS), Takotsubo cardiomyopathy, or stress-induced cardiomyopathy are interchangeable terms characterized by transient left ventricular systolic dysfunction, electrocardiographic changes, and cardiac biomarker elevation similar to acute coronary syndrome (ACS), without the presence of obstructive epicardial coronary artery disease. It predominantly affects postmenopausal females and manifests in the presence of stressful triggers such as severe physical or emotional stress, natural disasters, unexpected death of relatives, acute medical illnesses, etc. TTS was initially considered to be a benign condition however recent studies have shown that it may be associated with complications and mortality similar to ACS. Rare reports of TTS triggered by diabetic ketoacidosis (DKA) have been published. Herein we describe a case of an elderly female with a history of type II diabetes mellitus (DM) who was admitted with DKA and subsequently developed TTS that resolved after treatment of DKA and implementation of heart failure therapies.